The cryoablation for peripheral pulmonary lesions using a novel flexible bronchoscopic cryoprobe in the ex vivo pig lung and liver - Zheng, Xiaoxuan; Yang, Chi; Zhang, Xueyan; Yuan, Haibin; Xie, Fangfang; Li, Ying; Xu, Baikai; Herth, Felix; Sun, Jiayuan (Respiration, 2019)
Background: Percutaneous cryoablation has been used for the treatment of lung cancer and has been shown to be safe and effective. However, some lung cancer lesions cannot be reached by percutaneous puncture; using bronchoscopy cryoablation is necessary in these cases. Purposes: To examine the efficiency and security of a flexible cryoprobe, we measured the size and temperature distribution of the frozen area (ice ball) in ex vivo pig lung and liver and the temperature of the bronchoscope. Methods: We evaluated flexible cryoprobe cryoablation using a bronchoscope in ex vivo pig lung and a flexible cryoprobe alone in ex vivo pig liver. Seven temperature sensors were positioned at the surface of the cryoprobe and at distances of 0.3, 0.6, 0.9, 1.2, 1.5, and 1.8 cm from the cryoprobe. Two temperature sensors were positioned at the surface of the bronchoscope. The ex vivo pig lung and liver were perfused with 37 degrees C saline and the former was inflated using a ventilator to simulate in vivo lung conditions. The whole operation is usually 2-3 freezing cycles. Results: In ex vivo pig liver, probes made ice balls of 33.2 +/- 0.2 mm in diameter. In ex vivo pig lung, probes made ice balls of 35.1 +/- 1.7 mm in diameter. The temperature at the surface of the bronchoscope at distances of 1 and 10 cm from the cryoprobe reached 21.1 +/- 0.1 and 10.5 +/- 0.2 degrees C. Conclusion: A flexible cryoprobe using a bronchoscope in ex vivo pig lung and liver was a sufficiently safe treatment method. (c) 2019 S. Karger AG, Basel